2021
DOI: 10.1093/immadv/ltab011
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 immunity is maintained during cancer-associated adipose tissue wasting

Abstract: Cachexia is a systemic metabolic disorder characterized by loss of fat and muscle mass, which disproportionately impacts patients with gastrointestinal malignancies such as pancreatic cancer. While the immunologic shifts contributing to the development of other adipose tissue (AT) pathologies such as obesity have been well described, the immune microenvironment has not been studied in the context of cachexia. Here we assess the immune landscape of visceral AT (VAT) in the setting of pancreatic and colorectal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Immune cells can secrete cytokines and regulate the microenvironment of tissues. Healthy adipose tissue is characterized by a regulatory type 2 immune signature which suppresses inflammation and maintains adipocyte function ( 96 ). On the other hand, gene expression analysis of WAT showed increased levels of activated M2 macrophage markers and unchanged M1 markers, along with a significant increase in the number of macrophages in cachectic mice ( 19 , 21 ).…”
Section: The Impact Of Inflammation and Immune Cells On Adipose Tissuementioning
confidence: 99%
“…Immune cells can secrete cytokines and regulate the microenvironment of tissues. Healthy adipose tissue is characterized by a regulatory type 2 immune signature which suppresses inflammation and maintains adipocyte function ( 96 ). On the other hand, gene expression analysis of WAT showed increased levels of activated M2 macrophage markers and unchanged M1 markers, along with a significant increase in the number of macrophages in cachectic mice ( 19 , 21 ).…”
Section: The Impact Of Inflammation and Immune Cells On Adipose Tissuementioning
confidence: 99%
“…Due to the increased utilization of energy conserving pathways, fasting has especially anti-inflammatory effects, while highly energy consuming pro-inflammatory responses are downregulated (139, 143). Consistent with this, Lenehan et al found a decrease especially of Th1 and Th17 inflammation in wasting AT of tumor-bearing mice, while the Th2 response were maintained (144). Collectively, fasting has a supporting effect on Th2 responses, while the more energy consuming type 1 inflammatory responses are inhibited.…”
Section: Fastingmentioning
confidence: 68%
“…In the absence of glucose, activation of Th cells via Glut1 is impaired ( 8 ), but whether this also impairs Th2 cell function, which seems to be intact although glycolysis cannot be used ( 213 ), remains to be determined. Interestingly, a recent study showed that during cancer-associated adipose tissue wasting the Th2-environment in adipose tissue is maintained both in mice and humans ( 144 ).…”
Section: Th2 Cell Function During Obesity and Malnutritionmentioning
confidence: 99%
“…In this issue, Lenehan et al . shed light on the critical role of adipose tissue in regard to immune cell function, while providing a framework for future cancer therapy research [ 14 ]. They show the absence of a shift toward Th1 and Th17 inflammation and a maintained regulatory type-2 immunity in the adipose tissue of mice with cachexia.…”
Section: Immunometabolism As a Novel Strategy To Treat Disease: Recen...mentioning
confidence: 99%